2021
DOI: 10.1101/2021.06.30.450298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathology and immunity after SARS-CoV-2 infection in male ferrets is affected by age and inoculation route

Abstract: Improving COVID-19 intervention strategies partly relies on animal models to study SARS-CoV-2 disease and immunity. In our pursuit to establish a model for severe COVID-19, we inoculated young and adult male ferrets intranasally or intratracheally with SARS-CoV-2. Intranasal inoculation established an infection in all ferrets, with viral dissemination into the brain and gut. Upon intratracheal inoculation only adult ferrets became infected. However, neither inoculation route induced observable COVID-19 symptom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Yet, only a moderate inflammation in the nasal turbinates was observed, and no histopathology alterations were found in the lower respiratory tract. We assume, however, that the absence of pathology in the present study is due to the low level of productive infection when using the beta VOC, since effective SARS-CoV-2 viral replication frequently resulted in pathology manifestation in ferrets in other studies [19, 22, 23, 29, 30, 41].…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Yet, only a moderate inflammation in the nasal turbinates was observed, and no histopathology alterations were found in the lower respiratory tract. We assume, however, that the absence of pathology in the present study is due to the low level of productive infection when using the beta VOC, since effective SARS-CoV-2 viral replication frequently resulted in pathology manifestation in ferrets in other studies [19, 22, 23, 29, 30, 41].…”
Section: Discussionmentioning
confidence: 72%
“…In a previous study using SARS-CoV-2 with the D614G mutation, we observed inflammatory infiltration in the upper respiratory tract and hyperplasia of bronchus-associated lymphoid tissue in the lungs of infected male ferrets on 21 d.p.i. [23]. The late histopathology findings may reflect, in part, the extended signs and symptoms observed in human long-COVID.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations